Monitoring mangrove-based blue carbon ecosystems using UAVs: a review - Nurul Asyiqin Abu Bakar; Wan Shafrina Wan Mohd Jaafar; Khairul Nizam Abdul Maulud; Aisyah Marliza Muhmad Kamarulzaman; Siti Nor Maizah Saad; Midhun Mohan (Geocarto International)
Blue carbon habitats, including mangrove forests, salt marshes, and seagrass beds, play a crucial role in sequestering organic carbon, mitigating global warming, and protecting coastlines and local livelihoods. Traditional monitoring methods for these ecosystems are limited and expensive, leading to the adoption of remote sensing, particularly via unmanned aerial vehicles (UAVs). UAVs enhance monitoring efforts through high-resolution data collection, bolstering conservation and management strategies. This paper explores the utility of UAVs for monitoring mangrove-based blue carbon ecosystems, emphasizing their role in addressing emerging challenges. The review highlights the efficacy of UAVs in guiding conservation and restoration initiatives globally, especially in nations rich in mangrove ecosystems. Integration of artificial intelligence and machine learning further enhances UAV capabilities, facilitating data analysis and interdisciplinary collaboration. Advancements in UAV technology promise to revolutionize surveillance of mangrove-based blue carbon ecosystems, ensuring the protection of these vital habitats and their contribution to climate change mitigation.